Magnetorheological technology for fabricating tunable solid electrolyte with enhanced conductivity and mechanical property. (21st February 2018) - Peng, Gangrou; Ge, Yu; Ding, Jie; Wang, Caiyun; Wallace, Gordon G; Li, Weihua
Abstract: Ionogels are a new class of hybrid materials where ionic liquids are immobilized by macromolecular support. The excessive amount of crosslinking polymer enhances the mechanical strength but compromises the conductivity. Here, we report an elastomeric magnetorheological (MR) ionogel with an enhanced conductivity and mechanical strength as well. Following the application of magnetic nanoparticles into an ionic liquid containing minimum cross-linking agent, the formation, thus physical properties, of MR ionogels are co-controlled by simultaneously applied UV light and external magnetic field. The application of MR ionogels as solid electrolytes in supercapacitors is also demonstrated to study electrochemical performance. This work opens a new avenue to synthesize robust ionogels with the desired conductivity and controllable mechanical properties for soft flexible electronic devices. Besides, as a new class of conductive MR elastomers, the proposed MR ionogel also possesses the potential for engineering applications, such as sensors and actuators.